An efficient approach for sustainable fly ash geopolymer by coupled activation of wet-milling mechanical force and calcium hydroxide. (20th October 2022) - Yang, Jin; Tang, Yuanzhen; He, Xingyang; Su, Ying; Zeng, Jingyi; Ma, Mengyang; Zeng, Linghao; Zhang, Shaolin; Tan, Hongbo; Strnadel, Bohumír
Abstract: Geopolymer is a potential substitute for high-emission cement production. Therefore, the use of fly ash with high emission as a geopolymer is an environmentally friendly and inexpensive direction. However, fly ash (FA) is a high amorphous precursor with low pozzolanic reactivity making it difficult to be activated by calcium hydroxide. In this study, the coupling of wet-milling mechanical force and calcium hydroxide was used to prepare high-performance alkaline calcium activated geopolymers. Two kinds of FA slurries with different particle sizes of D50  = 2.96 μm and 14.2 μm were prepared, activated by calcium hydroxide (CH) with the content of 4%, 11% and 19%. Results indicated that the increase of calcium hydroxide content was beneficial to developing strength, effectively improving the chloride resistance, compacting the microstructure, but increasing the autogenous shrinkage of the geopolymers. These improvements are especially apparent in the wet-milled fly ash geopolymers (WFA) due to the pre-depolymerization implemented by wet-milled mechanical forces, and coupled with the activation effect of CH to improve the depolymerization efficiency and condensation reaction. The compressive strength of WF-CH-19 was three times higher than that of FA-CH-19, reaching 29.3 MPa at 28 d, and the compressive strength growth of WF-CH-11 even reached 591.67% at 1 d. Meanwhile, the main chain length (MCL) and Al/Si of calcium silicate hydrates were clearly improved, and pore structure was significantly refined with capillary pore increased from 29.79% to 89.23%. In addition, FA and WFA geopolymers have significant advantages over Portland cement in the environmental impact indicators such as E-energy and E-CO2 . Highlights: Low calcium FA geopolymer was prepared by coupling wet-milling mechanical force and CH activation. Compressive strength of WFA-CH-19% reached 29.3 MPa at 28 d, three times of FA-CH-19%. The growth rate of compressive strength is higher at low CH content. The critical pore size is reduced from 66.92 nm to 24.59 nm in WF-CH-19%. Significant increase in MCL and Al/Si ratio are found in WFA geopolymers.